Formation of Three-Way Scanning Electron Microscope Moiré on Micro/Nanostructures. (11th February 2014) - Wang, Qinghua; Kishimoto, Satoshi; Tsuda, Hiroshi
Abstract : Three-way scanning electron microscope (SEM) moiré was first generated using a designed three-way electron beam (EB) in an SEM. The spot-type three-way SEM moiré comes from the interference between the three-way EB and the specimen grating in which the periodic cells are arranged in a triangular manner. The deformation and the structure information of the specimen grating in three directions can be simultaneously obtained from the three-way SEM moiré. The design considerations of the three-way EB were discussed. As an illustration, the three-way SEM moiré spots produced on a silicon slide were presented. The proposed three-way SEM moiré method is expected to characterize micro/nanostructures in triangular or hexagonal arrangements in three directions at the same time.